More than just a gel: the extracellular matrixome of Pseudomonas aeruginosa - Nazeer, Rahan Rudland; Wang, Meng; Welch, Martin (Frontiers in Molecular Biosciences, 2023)
Armed with an arsenal of protein secretion systems, antibiotic efflux pumps, and the occasional proclivity for explosive self-destruction, Pseudomonas aeruginosa has become a model for the study of bacterial pathogenesis and biofilm formation. There is accruing evidence to suggest that the biofilm matrix—the bioglue that holds the structure together—acts not only in a structural capacity, but is also a molecular “net” whose function is to capture and retain certain secreted products (including proteins and small molecules). In this perspective, we argue that the biofilm matrixome is a distinct extracellular compartment, and one that is differentiated from the bulk secretome. Some of the points we raise are deliberately speculative, but are becoming increasingly accessible to experimental investigation.